Estudio de prefactibilidad para el diseño de un aplicativo móvil comparador de precios para fomentar las ventas y consumo de electrodomésticos en Lima Metropolitana - Chirinos Aguirre, Oswaldo Alejandro (2022)
The main objective of the project is to propose the design of a comparative application of appliance prices called "Lima Price" whose main functionality will be to collect information on prices of similar appliances belonging to department stores / retails and supermarkets allied to the application and present them on its platform to the end consumer. In this way, the application behaves as a link between the offering business and the user customer, promoting the increase in sales in the sector and providing the digital user with the first tool that allows them to compare prices quickly and efficiently, also rescuing other relevant variables. It will be personalized through the preferential factor method, that Lima will be the city where the project will be developed since, initially, only electrical appliances belonging to department stores/supermarkets and retail stores in Metropolitan Lima will be offered. In addition, it was defined that the demand of the project for the year 2022 is S/214 028 542, product of segmenting the DIA with the specifications of the target market derived from the applied survey. Regarding the microlocation, applying the factor ranking method, the district where the Lima Price work office will be implemented will be in Miraflores. Following this, considering the dimensioning of the service, the limiting factor is the size of the market, which consists of 713 428 browser users for the first year. Apart from this, the operation of the service was detailed through wireframes, allowing the functionalities of the application to be grounded and the concept offered to the user to be clearer. Finally, it was decreed that the project requires an investment of S/ 96 837 and when carrying out the economic and financial evaluation, an NPV of S/ 625 836,03 and S/ 677 580,32 was obtained, an IRR of 171% and 278%, respectively. Once this is defined, the hypothesis is validated given that there is a market for the service, and it is technically, socially, and economically feasible.